The PKI-FDR Uprising of 1948 and US Policy Regarding the Dutch-Indonesian Dispute - Richard Mason (Kajian Malaysia, 2009)
This paper contends that the abortive PKI-FDR uprising in Indonesia during the last quarter of 1948 marked an important turning point in the American policy toward the Indonesian struggle for independence against the Dutch. Before 1948, American policy toward Southeast Asia was almost exclusively dictated by the imperatives of European considerations, hence was pro-Dutch. The outbreak of the PKI-FDR not only raised the scepter of Communism in Indonesia but also underscored the belief Indonesian nationalism had to be settled in a just and practical way as a precondition to fight communism. In the final analysis, however, it cannot be said that the PKI-FDR revolt was ultimately responsible for the American decision to support the Indonesians. When threat of sanction was finally instituted against the Dutch, it was again European considerations which dictate the move